Water‐dispersible and soluble porous organic polymers for biomedical applications. Issue 5 (26th February 2022) - Tian, Jia; Lin, Furong; Yu, Shang‐Bo; Yu, Junlai; Tang, Qingxuan; Li, Zhan‐Ting
Abstract: Porous organic polymers (POPs) have become an emerging class of advanced porous organic materials owing to their structural diversity and tailored functions in solid state and organic media. Creating water‐soluble and related water‐dispersible POPs is still very challenging in the research area of porous organic materials. Their porosity‐based functions with diverse topological architectures in aqueous media offer promising platforms in bio‐related fields. This review highlights recent progress on water soluble or dispersible POPs for biomedical applications including bioimaging and biosensing, nanocarriers for drug delivery and tumor targeting, phototherapeutics, protein and gene delivery, biomacromolecule encapsulation and discrimination, and anti‐microbial activity. Abstract : Putting porosity into aqueous media, the water soluble organic polymers (ws‐POPs) provide us with a versatile platform for bio‐compatible structural engineering and functional exploration. According to the roles of the porosity played in various aqueous scenarios, recent biomedical applications including the bioimaging, drug delivery, cancer therapy, biomacromolecule delivery and discrimination, and anti‐microbial activity are summarized in this review.